Transport-Optimal Partitioning of a Region - Jaroslav Janacek (Communications - Scientific letters of the University of Zilina, 2000)
This paper deals with a problem of inhabited region partitioning. The partitioning is performed when a public administration system is changed. Location of subregion centres is usually connected with the partitioning. Both of these activities, the location subregions centres and forming of the subregions, have impacted public service accessibility. When the service provided to inhabitants is concentrated in the subregion centres, accessibility can be evaluated and the problem of optimal partitioning and centre location can be solved. This paper shows various partitioning problems and reports on associated solution techniques and results obtained for real-sized instances.